2016
DOI: 10.1097/md.0000000000002625
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Predictive of Recurrence and Progression for Patients Who Suffered Initial Recurrence After Transurethral Resection of Stage pT1 Bladder Tumor in Chinese Population

Abstract: Bladder cancer is one of the most common malignancies worldwide and the stage pT1nonmuscle invasive bladder cancer (NMIBC) has a high probability of recurrence after initial diagnosis and treatment. However, risk factors predictive of repeated recurrence and progression of pT1 bladder tumors after primary relapse have not been uncovered. Thus, we conducted the retrospective study.A total of 418 patients who suffered initial recurrence after transurethral resection (TUR) of pT1 bladder tumor were selected for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…Initial tumor size, tumor multifocality, tumor grade, history of recurrence, a shorter timing of intravesical therapy, and presence of CIS are all disease specific variables associated with recurrence [14][15][16]. Similarly, in our cohort, tumor size, tumor multifocality, and the presence of concomitant CIS were associated with higher odds of recurrence and time to recurrence for NMIBC recurrence.…”
Section: Discussionsupporting
confidence: 65%
“…Initial tumor size, tumor multifocality, tumor grade, history of recurrence, a shorter timing of intravesical therapy, and presence of CIS are all disease specific variables associated with recurrence [14][15][16]. Similarly, in our cohort, tumor size, tumor multifocality, and the presence of concomitant CIS were associated with higher odds of recurrence and time to recurrence for NMIBC recurrence.…”
Section: Discussionsupporting
confidence: 65%
“…This approach was adopted in several similar studies, e.g. by Shen et al [15] Our systematic analysis has also shown the inconsistency in reporting the validity of utilized stratification approaches. For example, very recent analysis of 301 patients by Wang et al [16] or the analysis of 1436 patients by Rieken et al [17] (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The individual surgeon has a significant impact on the risk of recurrence after curative treatment of patients with NMIBC, as described previously, 13 and another approach could aggravate the lead-time bias. A similar reasoning has been adopted in several similar studies 14 Our systematic analysis also demonstrates the inconsistency in reporting the validity of utilized stratification approaches. For example, neither the very recent analysis of 301 patients by Wang et al 15 nor an analysis of 1436 patients, a group without immediate postoperative instillation of chemotherapy, by Rieken et al 16 could be included in the review due to lack of c-index or AUCROC analysis.…”
Section: Discussionmentioning
confidence: 63%
“…The individual surgeon has a significant impact on the risk of recurrence after curative treatment of patients with NMIBC, as described previously, 13 and another approach could aggravate the lead‐time bias. A similar reasoning has been adopted in several similar studies 14 …”
Section: Discussionmentioning
confidence: 92%